Electrochromic Devices

JP7651163B2Active Publication Date: 2025-03-26UNIV OF HYOGO
View PDF 14 Cites 0 Cited by

Patent Information

Application Number
JP2021051935
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Filing Date
2021-03-25
Publication Date
2025-03-26
Estimated Expiration
2041-03-25

AI Technical Summary

Benefits of technology

【0024】 本発明の二電極系エレクトロクロミックデバイスは、作用電極基板と対電極との間には、エレクトロクロミック層と電解質層の二層が存在するだけでよい。また本発明の三電極系エレクトロクロミックデバイスは、作用電極基板と対電極との間には、エレクトロクロミック層と電解質が存在するだけでよい。そして、エレクトロクロミック化合物となる非対称型金属錯体を電極基板にスピンコートすることのみでエレクトロクロミック層を形成することができる。そのため、従来のエレクトロクロミックデバイスと比較すると大幅に簡略化された構造であり、製造工程を大幅に簡素化し得る。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 0007651163000027
    Figure 0007651163000027
  • Figure 0007651163000028
    Figure 0007651163000028
  • Figure 0007651163000029
    Figure 0007651163000029
Patent Text Reader

Abstract

To provide an electrochromic device in which a thin film consisting of a single molecule can be prepared by a solution method, and an asymmetric metallic complex compound showing a multicolor electrochromism by an electrochemical redox reaction is introduced.SOLUTION: An electrochromic device of the present invention includes; a working electrode; a counter electrode; an electrolyte layer: and an electrochromic layer consisting of an electrochromic compound having a structure of the chemical formula 1. The electrochromic layer is formed on the substrate surface of the working electrode. In the formula 1, R1 and R2 are each a C5-C12 alkyl group, M is Pt or Au, and X1 and X2 are C or N respectively.SELECTED DRAWING: None
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to an electrochromic device that uses, as an electrochromic compound, an asymmetric metal complex in which a bidentate ligand having a nitrogen-containing heteroaromatic group and a sulfur-containing π-electron extended ligand are coordinated to a metal ion. [Background technology]

[0002] Electrochromism is a phenomenon in which the color or transmittance of a compound reversibly changes due to an electrochemical oxidation-reduction reaction, and electrochromic devices incorporating electrochromic compounds have been put to practical use in displays and light-control glass, particularly light-blocking glass for aircraft (Patent Document 1 and Patent Document 2).

[0003] In recent years, electrochromic materials have been attracting attention as display materials. As such electrochromic materials, various organic / metal hybrid polymers formed from terpyridine as a metal-acting compound and metal ionization have been developed, and electrochromic devices using them have been reported (Patent Documents 3 to 5). For example, Patent Documents 3 and 4 disclose organic / metal hybrid polymers in which the organic ligand is a terpyridine group or a phenanthroline group and a metal ion is coordinated to the organic ligand, and electrochromic devices using the same.

[0004] In addition, electrochromic display elements having polymer compounds such as polyaniline, polyaniline derivatives, polypyrrole, polypyrrole derivatives, polythiophene, and polythiophene derivatives between layers of layered clay minerals, and nanoparticle-conductive polymer composites (Patent Document 6, Patent Document 7, Non-Patent Document 1), and electrochromic display elements having a thin film of metal oxide or metal nanoparticles have also been developed (Patent Document 8). [Prior art documents] [Patent documents]

[0005] [Patent Document 1] US Patent Application Publication No. 2013 / 0182308 [Patent Document 2] European Patent No. 1330678 [Patent Document 3] JP 2018-30912 A [Patent Document 4] JP 2007-112957 A [Patent Document 5] JP 2012-188517 A [Patent Document 6] Japanese Patent Application Publication No. 10-239714 [Patent Document 7] JP 2019-12845 A [Patent Document 8] Special table 2019-552264 publication [Patent Document 9] JP 2018-92153 A [Patent Document 10] International Publication No. 2018 / 016385 [Non-patent literature]

[0006] [Non-Patent Document 1] “Electrochromic Materials”, Roger J. Mortimer, Annual Review of Material Research, 2011, 41, 241-268. [Non-Patent Document 2] “Preparation of Pt(II) and Pd(II) complexes coordinated with both a diimine ligand and a sulfur-rich dithiolate ligand and electrical conductivities of their oxidized species and X-ray crystal structure of Pd(N-butyl-pyridine- 2-carbaldimine)(C3S5)”, Kazuya Kubo, Motohiro Nakano, Hatsue Tamura, Gen-etsu Matsubayashi, Inorganica Chimica Acta, 2000, 311, 6-14. [Non-Patent Document 3] “Preparation and oxidation of polarized Au(III) complexes having both the C-deprotonated-2-phenylpyridine (ppy) and a sulfur-rich dithiolate ligand and X-ray crystal structure of [Au(η2-C,N-ppy)(η2-S,S-C8H4S8)]·0.5DMF”, Kazuya Kubo, Motohiro Nakano, Hatsue Tamura, Gen-etsu Matsubayashi, Masami Nakamoto, Journal of Organometallic Chemistry, 2003, 669, 141-148. [Non-Patent Document 4] “Preparation and Oxidation of Pt(II) Complexes Containing Both C-Deprotonated 2-Phenylpyridine (ppy-) and a Sulfur-Rich Dithiolate Ligand and X-ray Crystal Structure of [NBun4][Pt(ppy)(C8H4S8)]”, Suga Yusuke, Nakano Motohiro, Tamura Hatsue, Matsubayashi Gen-etsu, Bulletin of the Chemical Society of Japan, 2004, 77, 1877-1883. [Non-Patent Document 5] “Unique Solvatochromic Behavior of Unsymmetrical Platinum-Dithiolene Complexes Coordinated by 4,4'-Dinonyl-2,2'-Bipyridine”, Hori Aoi, Kim Yuna, Tahara Keishiro, Kadoya Tomofumi, Yamada Jun-ichi, Kubo Kazuya, 2020, accepted, doi.org / 10.1002 / ejic.202001014. [Non-Patent Document 6] “Highly Efficient, Near-Infrared and Visible Light Modulated Electrochromic Devices Based on Polyoxometalates and W18O49 Nanowires” Hongxi Gu, Chongshen Guo, Shouhao Zhang, Lihua Bi, Tianchan Li, Tiedong Sun and Shaoqin Liu, ACS Nano 2018, 12, 559-567. Summary of the Invention [Problem to be solved by the invention]

[0007] A conventional electrochromic device has a basic layered structure consisting of a first electrode, an electrochromic layer located on the first electrode and containing at least one of organic / metal hybrid polymers, polyaniline, polyaniline derivatives, polypyrrole, polypyrrole derivatives, polythiophene, and polythiophene derivative polymer compounds, or nanoparticle-conductive polymer composites, an electrolyte layer located on the electrochromic layer, and a second electrode located on the electrolyte layer. In order to stabilize such an electrochromic device, it is necessary to form a composite in which an organic polymer is laminated on the electrochromic layer (Patent Document 3). The organic polymer layer requires at least one selected from the group consisting of conductive polymers, polypyrrole, polyaniline, polythiophene, poly(p-phenylene), poly(3,4-ethylenedioxythiophene)-poly(styrenesulfonate) (PEDOT:PSS), polyfluorene, poly(p-phenylenevinylene), polythienylenevinylene, and organic / metal hybrid polymers.

[0008] In addition, in conventional electrochromic devices, a two-color change or coloring / decoloring process occurs due to one-electron oxidation-reduction of the electrochromic layer introduced. Therefore, in order to construct a multicolor electrochromic device that emits three or more colors, it is necessary to construct a device in which the above-mentioned basic structure of the electrochromic device is laminated, or to construct an electrochromic layer in which multiple electrochromic materials are mixed (for example, Patent Document 9, Patent Document 10, or Non-Patent Document 1).

[0009] Furthermore, the formation of thin films when mounting conventional electrochromic compounds on devices requires complicated fabrication processes, such as polymerization on a substrate and compounding with various polymer compounds, etc. These factors are currently hindering the development of industrial applications of electrochromic devices.

[0010] The present invention aims to provide an electrochromic device that incorporates an asymmetric metal complex compound that can be prepared by a solution process as a thin film made of a single molecule and that exhibits multicolor electrochromism through an electrochemical oxidation-reduction reaction. [Means for solving the problem]

[0011] In order to construct a conductor using a molecular crystal, the present inventors developed asymmetric low molecular weight metal complex molecules in which a bidentate ligand having a nitrogen-containing heteroaromatic ring and a sulfur-containing π-electron extended ligand are coordinated to a metal ion, as shown in Non-Patent Documents 2 to 4. Then, as a result of extensive research into whether these asymmetric low molecular weight metal complex molecules can be used as electrochromic compounds, they found that certain asymmetric low molecular weight metal complex molecules have properties that are preferable as electrochromic compounds, and thus completed the present invention.

[0012] Specifically, the present invention provides A working electrode; A counter electrode; An electrolyte layer; and an electrochromic layer made of an electrochromic compound having a structure of Chemical Formula 1; the electrolyte layer and the electrochromic layer are sandwiched between the working electrode and the counter electrode; The electrochromic layer is formed so as to be in contact with the working electrode, The electrolyte layer is formed so as to be in contact with the counter electrode, A voltage is applied between the working electrode and the counter electrode to change the color of the electrochromic layer. This relates to electrochromic devices (two-electrode electrochromic devices).

[0013] The present invention also provides A cell, A working electrode; A counter electrode; A reference electrode; An electrolyte; An electrochromic layer made of an electrochromic compound having a structure of Chemical Formula 1; having The working electrode has the electrochromic layer formed on one surface of a substrate, the counter electrode and the reference electrode are located in the cell at positions opposite the electrochromic layer of the working electrode; The cell is filled with the electrolyte, A voltage is applied between the working electrode and the counter electrode to change the color of the electrochromic layer. This relates to electrochromic devices (three-electrode electrochromic devices).

[0014] [ka]

[0015] In chemical formula 1, R 1 and R 2 are each a C5 to C12 alkyl group, M is Pt or Au; X 1 and X 2 are C or N, respectively.

[0016] The present inventors have discovered that an asymmetric low molecular weight metal complex molecule represented by Chemical Formula 1 is 1) Has an absorption band in the visible light region or near infrared region; 2) It is stable against electrochemical oxidation and reduction; 3) The above absorption band reversibly changes wavelength and transmittance through electrochemical oxidation / reduction; 4) It has electrical conductivity or can have electrical conductivity by being composited with a conductive organic polymer or the like; 5) Thin films with thicknesses of 10 nm to 1000 nm can be formed; It was found for the first time that the compound has such suitable properties as an electrochromic compound.

[0017] The electrochromic device of the present invention is characterized in that it utilizes a specific asymmetric metal complex as an electrochromic compound, and these electrochromic compounds are soluble in various organic solvents and can be formed into thin films by solution methods such as spin coating or drop casting. The electrochromic compounds used in the present invention also exhibit concerted electrochromic behavior in the near infrared region correlated with the visible light region through electrochemical redox reactions. Furthermore, the electrochromic device of the present invention, which is fabricated in a simple two-electrode structure, exhibits stable switching characteristics and multicolor electrochromism.

[0018] The electrochromic compound used in the present invention is preferably of either formula 2 or 3.

[0019] [ka]

[0020] [ka]

[0021] In the two-electrode electrochromic device and the three-electrode electrochromic device, the thickness of the electrochromic layer is preferably 10 nm or more and 1000 nm or less.

[0022] In a two-electrode electrochromic device, the thickness of the electrolyte layer is preferably 100 nm or more and 200 μm or less.

[0023] The electrolyte layer is preferably an ionic liquid, a polymer gel, a photopolymerizable polymer solid or a thermally polymerizable polymer solid, and is most preferably an ionic liquid. Effect of the Invention

[0024] In the two-electrode electrochromic device of the present invention, only two layers, an electrochromic layer and an electrolyte layer, are required between the working electrode substrate and the counter electrode. In the three-electrode electrochromic device of the present invention, only an electrochromic layer and an electrolyte are required between the working electrode substrate and the counter electrode. The electrochromic layer can be formed by simply spin-coating an asymmetric metal complex, which is an electrochromic compound, onto the electrode substrate. Therefore, the structure is significantly simplified compared to conventional electrochromic devices, and the manufacturing process can be significantly simplified. [Brief description of the drawings]

[0025] [Figure 1] 1 shows a photograph of the appearance of an electrochromic layer (compound 2) formed on an ITO glass substrate. [Diagram 2] FIG. 1 shows a schematic diagram of a three-electrode measurement cell (three-electrode electrochromic device). [Diagram 3] FIG. 1 shows a schematic diagram of an electrochromic property measuring device. [Figure 4] 1 shows a conceptual diagram illustrating the direction of light transmission through a cell in a spectrophotometer. [Diagram 5] The color changes of compounds 2, 5, 10, 11, and 12 in the neutral, one-electron acid, and two-electron oxidized states are shown. [Figure 6] The redox potential of the thin film of compound 2 was measured in the range of -0.5 to +1.2 V (vs. Ag / AgCl) at a sweep rate of 0.01 V / sec. (a) shows the result of a 3-cycle measurement, and (b) shows the result of an 8-cycle measurement. [Figure 7] The following graphs show the spectral changes during the oxidation and reduction processes of compound 2 when voltages of -0.5, +0.2, and +1.2 V (vs. Ag / AgCl) are applied. (a) shows the oxidation process, and (b) shows the reduction process. [Figure 8]The redox potential of the thin film of compound 5 was measured in the range of -0.2 to +1.5 V (vs. Ag / AgCl) at a sweep rate of 0.01 V / sec. (a) shows the result of a 3-cycle measurement, and (b) shows the result of a 9-cycle measurement. [Figure 9] The spectral changes of compound 5 are shown when voltages of -0.2, +0.71, and +1.2 V (vs. Ag / AgCl) are applied during the oxidation process, and voltages of +1.2 V, +0.44, -0.2, and (vs. Ag / AgCl) are applied during the reduction process. (a) shows the oxidation process, and (b) shows the reduction process. [Figure 10] The switching characteristics of compound 2 were measured at 584 nm in the visible light region and 892 nm in the near infrared region at applied voltages of +0.9 V (vs. Ag / AgCl) and +0.35 V (vs. Ag / AgCl) with a pulse width of 10 seconds. (a) shows the oxidation process, and (b) shows the reduction process. [Figure 11] (a) shows the results of measuring the switching characteristics of Compound 5 in the visible light region of 660 nm at applied voltages of +0.6 V (vs. Ag / AgCl) and -0.5 V (vs. Ag / AgCl) with a voltage pulse width of 10 seconds, and (b) shows the results of measuring the switching characteristics of Compound 5 in the near-infrared region of 900 nm at applied voltages of +1.2 V (vs. Ag / AgCl) and +0.6 V (vs. Ag / AgCl) with a voltage pulse width of 10 seconds. [Figure 12] FIG. 1 shows a schematic diagram of a two-electrode electrochromic device. [Figure 13] FIG. 1 shows a schematic diagram of the spectroscopic setup used for the two-electrode based electrochromic device. [Figure 14] The results of measuring the electrochromic behavior when a voltage was reversibly applied between the working electrode and the counter electrode of a two-electrode device of Compound 2 in the range of +2.0 V to −1.4 V, starting from a potential of 0 V, are shown. [Figure 15]The starting potential was 0 V, and the potential between the working electrode 1 and the counter electrode 2 of a two-electrode device of compound 5 was oxidized to +3.0 V via +1.8 V based on 0 V, and then the potential was reversed and reduced to -1.4 V via +1.8 V, and then oxidized again to 0 V. The results of measuring the electrochromic behavior are shown in the figures. [Figure 16] (a) shows the switching behavior of compound 2 at 584 nm (visible light region), and (b) shows the switching behavior of compound 2 at 1020 nm (near infrared region). [Figure 17] (a) shows the switching behavior of compound 5 at 730 nm (visible light region), and (b) shows the switching behavior of compound 5 at 940 nm (near infrared region). DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0026] DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS The present invention will now be described with reference to the accompanying drawings.

[0027] <Electrochromic compounds> As the electrochromic compounds, the following compounds 1 to 13 were used.

[0028] (Compound 1) Compound 1 is a complex of the nitrogen-containing ligand 2,2'-bipyridine (bpy) and the sulfur-containing ligand 2-{(4,5-ethylenedithio)-1,3-dithiole-2-ylidene}-1,3-dithiole-4,5-ditholate(2-) (C 8 H 4 S 8 2- ) is an asymmetric metal complex in which platinum(II) ions are coordinated, and [(bpy)Pt(C 8 H 4 S 8 )] (Non-Patent Document 2).

[0029] Under an argon atmosphere, metallic sodium (93 mg, 4.0 mmol) and the sulfur-containing ligand 2-{(4,5-ethylenedithio)-1,3-dithiole-2-ylidene}-1,3-dithiole-4,5-ditholate(2-) (C 8 H 4 S 8 2- ) precursor (C 8 H 4 S 8 (C 2 H 4 CN) 2 ) (230 mg, 0.50 mmol) was dissolved in ethanol (40 mL). The resulting deep red solution was treated with the metal complex precursor Pt(bpy)Cl 2 (190 mg, 0.45 mmol) (bpy = 2,2'-bipyridine) in dimethyl sulfoxide (20 cm 3 The mixture was added to the 1,2-dichlorophenyl ether (1,2-dichlorophenyl ether) solution and reacted with the mixture, followed by stirring for 30 minutes. The resulting dark blue powder was filtered under reduced pressure. The resulting dark blue powder was washed with methanol and diethyl ether in that order, and dried under reduced pressure to obtain compound 1. Yield: 67%.

[0030] Elemental analysis results: Calc. for C 18 H 12 N 2 PtS 8 : C, 30.54; H, 1.71; N, 3.96. Found: C, 30.38; H, 1.89; N, 3.97%. l H-NMR (dimethyl sulfoxide-d 6 , 50 °C): δ(ppm) 3.37 (s, 4H), 7.74 (t, 2H), 3.3 (t, 4H), 2.84 (t, 4H), 7,74 (t, 2H), 8,35 (t, 2H), 8.62 (d, 2H), 8.87 (d, 2H; 2 J ( 195 Pt- l H), 36 Hz).

[0031] [ka]

[0032] (Compound 2) Compound 2 is a cationically linked cationically linked 2,2'-bipyridine (bpy) with a nitrogen-containing ligand, 2-{bis(decylthio)-1,3-dithiole-2-ylidene}-1,3-dithiole-4,5-dithiolate(2-) (C10-C 6 S 8 2- ) is an asymmetric metal complex in which platinum(II) ions are coordinated with [(bpy)Pt(C10-C 6 S 8 )] (Non-Patent Document 2).

[0033] Under an argon atmosphere, metallic sodium (130 mg, 5.7 mmol) and the precursor of the sulfur-containing ligand 2-{bis(decylthio)-1,3-dithiole-2-ylidene}-1,3-dithiole-4,5-dithiolate (2-) (C10-C 6 S 8 (CH 2 CH 2 COOC 2 H 5 ) 2 (600 mg, 0.76 mmol) was dissolved in ethanol (50 mL) to obtain a deep red solution, which was then mixed with the metal complex precursor Pt(bpy)Cl 2 (310 mg, 0.73 mmol) (bpy = 2,2'-bipyridine) in dimethyl sulfoxide (50 cm 3 ) solution and reacted and stirred for 30 minutes. The resulting dark green powder was filtered off under reduced pressure. The resulting dark green powder was dissolved in chloroform and purified by filtering through silica gel. The green solution obtained after filtration was concentrated, and methanol was added to precipitate a green powder. The green powder obtained by suction filtration using a glass filter was washed with methanol and diethyl ether in that order, and dried under reduced pressure to obtain compound 2. Yield: 25%.

[0034] Elemental analysis results: Calc. for C 36 H 50 N 2 PtS 8 : C, 44.92; H, 5.23; N, 2.91. Found: C, 44.44; H, 5.17; N, 2.99%. l H-NMR (dimethyl sulfoxide-d 6 , 50 °C): δ(ppm) 0.84 (t, 6H), 1.36 (m, 28H), 1,57 (t, 4H), 2.84 (t, 4H), 7,74 (t, 2H), 8,36 (t, 2H), 8.62 (d, 2H), 8.87 (d, 2H; 2 J ( 195 Pt- l H), 41 Hz).

[0035]

Chem.

[0036] (Compound 3) Compound 3 is an asymmetric metal complex in which the nitrogen-containing ligand N-butyl-pyridine-carbaldimine (Bu-pya) and the sulfur-containing ligand 2-{(4,5-ethylenedithio)-1,3-dithiole-2-ylidene}-1,3-dithiole-4,5-ditholate(2-)(C 8 H 4 S 8 2- ) coordinate to platinum(II) ions, and is denoted as [(Bu-pya)Pt(C 8 H 4 S 8 )] (Non-Patent Document 2).

[0037] Under an argon atmosphere, metallic sodium (100 mg, 4.3 mmol) and the precursor of the sulfur-containing ligand 2-{(4,5-ethylenedithio)-1,3-dithiole-2-ylidene}-1,3-dithiole-4,5-ditholate (2-) (C 8 H 4 S 8 (C 2 H 4 CN) 2 ) (180 mg, 0.39 mmol) was dissolved in ethanol (50 mL). The resulting deep red solution was treated with the metal complex precursor Pt(Bu-pia)Cl 2 (160 mg, 0.37 mmol) (Bu-pya = N-butyl-pyridine-carbaldimine) in ethanol (250 cm 3 ) solution and reacted, then stirred for 30 minutes. The resulting black powder was filtered off under reduced pressure, and the solid was washed successively with methanol and diethyl ether. The resulting black powder was further purified by dissolving it in chloroform and filtering through silica gel. The green solution obtained after filtration was concentrated, and methanol was added to precipitate a dark blue powder. The dark blue powder obtained by suction filtration using a glass filter was washed successively with methanol and diethyl ether, and dried under reduced pressure to obtain compound 3. Yield: 20%.

[0038] Elemental analysis results: Calc. for C 18 H 18 N 2 PtS 8 : C, 30.28; H, 2.54; N, 3.92. Found: C, 30.12; H, 2.55; N, 3.75%. l H-NMR (dimethyl sulfoxide-d 6, 50 °C): δ(ppm) 0.93 (t, 3H), 1.35 (m, 2H), 1.87 (t, 2H), 3.34 (s, 4H), 4.10 (t, 2H), 7.73 (t, 1H), 8.10 (d, 1H), 8.26 (t, 1H), 8.87 (d, 1H; 2 J ( 195 Pt- l H), 38 Hz), 9.40 (s, 1H; 2 J ( 195 Pt- l H), 75 Hz).

[0039] [ka]

[0040] (Compound 4) Compound 4 is a complex of the nitrogen-containing ligand C-deprotonated-2-phenylpyridine (ppy) and the sulfur-containing ligand 2-{(4,5-ethylenedithio)-1,3-dithiole-2-ylidene}-1,3-dithiole-4,5-ditholate(2-)(C 8 H 4 S 8 2- ) is an asymmetric metal complex in which gold(III) ions are coordinated, and [(ppy)Au(C 8 H 4 S 8 )] (Non-Patent Document 3).

[0041] Under an argon atmosphere, metallic sodium (26 mg, 1.1 mmol) and the sulfur-containing ligand 2-{(4,5-ethylenedithio)-1,3-dithiole-2-ylidene}-1,3-dithiole-4,5-ditholate(2-) (C 8 H 4 S 8 2- ) precursor (C 8 H 4 S 8 (C 2 H 4 CN)2 ) (230 mg, 0.50 mmol) was dissolved in ethanol (15 mL). The resulting deep red solution was treated with the metal complex precursor Au(ppy)Cl 2 (120 mg, 0.30 mmol) (ppy = C-deprotonated-2-phenylpyridine) in N,N-dimethylformamide (10 cm 3 The mixture was added to the 100% ethyl acetate solution and reacted with 100% ethyl acetate, and stirred for 12 hours. The brown powder was filtered under reduced pressure. The brown powder was washed with methanol and dried under reduced pressure to obtain compound 4. Yield: 83%.

[0042] Elemental analysis results: Calc. for C 19 H 12 AuNS 8 : C, 32.24; H, 1.71; N, 1.98. Found: C, 32.35; H, 1.86; N, 2.22%. l H-NMR (dimethyl sulfoxide-d 6 , 50 °C): δ(ppm) 3.39 (s, 4H), 7.40 (t, 1H), 7.47 (t, 1H), 7.52 (d, 1H), 7.68 (t, 1H), 8.06 (d, 1H), 8.35 (t, 1H), 8.44 (d, 1H), 8.75 (d, 1H).

[0043] [ka]

[0044] (Compound 5) Compound 5 is a cationically linked cationically linked 2-phenylpyridine (PPY) and 2-{bis(decylthio)-1,3-dithiole-2-ylidene}-1,3-dithiole-4,5-dithiolate(2-) (C10-C 6 S 8 2-) is an asymmetric metal complex in which gold(III) ions are coordinated, and [(ppy)Au(C 10 -C 6 S 8 )] (Non-Patent Document 3).

[0045] Under an argon atmosphere, metallic sodium (27 mg, 1.2 mmol) and the precursor of the sulfur-containing ligand 2-{bis(decylthio)-1,3-dithiole-2-ylidene}-1,3-dithiole-4,5-dithiolate(2-) (C10-C 6 S 8 (CH 2 CH 2 COOC 2 H 5 ) 2 (400 mg, 0.50 mmol) was dissolved in ethanol (90 mL). The resulting deep red solution was treated with the metal complex precursor Au(ppy)Cl 2 (160 mg, 0.38 mmol) (ppy = C-deprotonated-2-phenylpyridine) in N,N-dimethylformamide (15 cm 3 ) solution and reacted, and stirred for 17 hours. The resulting reddish brown powder was filtered off under reduced pressure. The resulting reddish brown powder was dissolved in chloroform and purified by filtering through silica gel. The reddish brown solution obtained after filtration was concentrated, and methanol was added to precipitate the reddish brown powder. The reddish brown powder obtained by suction filtration using a glass filter was washed with methanol and diethyl ether in that order, and dried under reduced pressure to obtain compound 5. Yield: 74%.

[0046] Elemental analysis results: Calc. for C 37 H 50 AuNS 8 : C, 46.18; H, 5.24; N, 1.46. Found: C, 45.80; H, 5.22; N, 1.49%. 1H-NMR (chloroform-d, 25 °C): d (ppm) 0.81 (t, 6H), 1.13 (m, 24H), 1.34 (t, 4H), 1.59 (t, 4H), 2.78 (t, 4H), 7.08 (t, 1H), 7.23 (m, 3H), 7.56 (d, 1H), 7.81 (d, 1H), 7.92 (t, 1H), 8.62 (d, 1H).

[0047] [ka]

[0048] (Compound 6) Compound 6 is a cationically substituted aryl group consisting of the nitrogen-containing ligand C-deprotonated-2-phenylpyridine (ppy) and the sulfur-containing ligand 2-{(4,5-ethylenedithio)-1,3-dithiole-2-ylidene}-1,3-dithiole-4,5-ditholate(2-)(C 8 H 4 S 8 2- ) is an asymmetric metal complex in which platinum(II) ions are coordinated, and tetraethylammonium [(ppy)Pt(C 8 H 4 S 8 )] (Non-Patent Document 4).

[0049] Under an argon atmosphere, metallic sodium (62 mg, 2.7 mmol) and the sulfur-containing ligand 2-{(4,5-ethylenedithio)-1,3-dithiole-2-ylidene}-1,3-dithiole-4,5-ditholate(2-) (C 8 H 4 S 8 2- ) precursor (C 8 H 4 S 8 (C 2 H 4 CN) 2) (250 mg, 0.52 mmol) was dissolved in ethanol (90 mL). The resulting deep red solution was treated with the metal complex precursor [{Pt(ppy)Cl} 2 ] (200 mg, 0.26 mmol) (ppy = C-deprotonated-2-phenylpyridine) and tetraethylammonium bromide (440 mg, 2.1 mmol) in dimethyl sulfoxide (10 cm 3 The mixture was added to the 1,2-dichlorophenyl ether (1,2-dichlorophenyl ether) solution, reacted, and stirred for 3 hours. The reddish purple powder was separated by filtration under reduced pressure. The obtained reddish purple powder was washed with methanol and dried under reduced pressure to obtain compound 6. Yield 85%.

[0050] Elemental analysis results: Calc. for C 27 H 32 N 2 PtS 8 : C, 44.33; H, 5.10; N, 2.95. Found: C, 43.85; H, 4.88; N, 3.03%. l H-NMR (dimethyl sulfoxide-d 6 , 25 °C):δ(ppm) 1.15 (t, 12H), 3.18 (q, 8H), 3.30 (s, 4H), 7.01 (m, 2H), 7.23 (m, 1H), 7.53 (d, 1H; 2 J ( 195 Pt- l H), 40 Hz), 7.68 (d, 1H), 7.98 (d, 1H), 8.01 (d, 1H), 8.85 (d, 1H; 2 J ( 195 Pt- l H), 33 Hz).

[0051] [ka]

[0052] (Compound 7) Compound 7 consists of the nitrogen-containing ligand C-deprotonated-2-phenylpyridine (ppy) and the sulfur-containing ligand disulfanyl-1,3-dithiol-2-thionate ( 2- ) (C 3 S 5 2- ) is an asymmetric metal complex in which platinum(II) ions are coordinated, and tetraethylammonium [(ppy)Pt(C 3 S 5 )] (Non-Patent Document 4). The sulfur-containing ligand disulfanyl-1,3-dithiol-2-thionate ( 2- ) is also written as 2-thione-1,3-dithiole-4,5-dithiolate.

[0053] Under an argon atmosphere, metallic sodium (62 mg, 2.7 mmol) and the sulfur-containing ligand disulfanyl-1,3-dithiol-2-thionate(2-) (C 3 S 5 2- ) precursor (C 3 S 5 (C 2 H 4 CN) 2 ) (160 mg, 0.52 mmol) was dissolved in ethanol (90 mL). The resulting deep red solution was treated with the metal complex precursor [{Pt(ppy)Cl} 2 ] (200 mg, 0.26 mmol) (ppy = C-deprotonated-2-phenylpyridine) and tetraethylammonium bromide (440 mg, 2.1 mmol) in dimethyl sulfoxide (1.0 cm 3 The mixture was added to the 1,2-dichlorophenyl ether solution and reacted with the 1,2-dichlorophenyl ether solution, and stirred for 3 hours. The reddish purple powder was separated by filtration under reduced pressure. The obtained reddish purple powder was washed with methanol and dried under reduced pressure to obtain compound 7. Yield: 15%.

[0054] Elemental analysis results: Calc. for C 22 H 28 N 2 PtS5 : C, 39.10; H, 4.18; N, 4.14. Found: C, 38.94; H, 4.22; N, 4.19%. l H-NMR (dimethyl sulfoxide-d 6 , 25 °C):δ(ppm) 1.15 (t, 12H), 3.18 (q, 8H), 7.01 (m, 2H), 7.23 (m, 1H), 7.53 (d, 1H; 2 J ( 195 Pt- l H), 40 Hz), 7.68 (d, 1H), 7.98 (d, 1H), 8.01 (d, 1H), 8.85 (d, 1H; 2 J ( 195 Pt- l H), 33 Hz).

[0055] [ka]

[0056] (Compound 8) Compound 8 is a complex of the nitrogen-containing ligand N-butyl-pyridine-carbaldimine (Bu-pya) and the sulfur-containing ligand 2-{(4,5-ethylenedithio)-1,3-dithiole-2-ylidene}-1,3-dithiole-4,5-ditholate(2-)(C 8 H 4 S 8 2- ) is an asymmetric metal complex in which palladium(II) ions are coordinated, and [(Bu-pya)Pd(C 8 H 4 S 8 )] (Non-Patent Document 2).

[0057] Under an argon atmosphere, a 25% methanol solution of tetramethylammonium hydroxide (25 mL) and the precursor of the sulfur-containing ligand 2-{(4,5-ethylenedithio)-1,3-dithiole-2-ylidene}-1,3-dithiole-4,5-ditholate (2-) (C 8 H 4 S 8 (C 2 H 4 CN) 2 ) (780 mg, 1.7 mmol) was dissolved in tetrahydrofuran (50 mL). The resulting pale red solid was filtered off. The resulting pale red solid was dissolved in ethanol (50 mL) and the metal complex precursor Pd(Bu-pia)Cl 2 (160 mg, 0.37 mmol) (Bu-pya = N-butyl-pyridine-carbaldimine) was added to a solution of ethanol (100 mL) and the mixture was stirred for 30 minutes. The resulting dark green powder was filtered off under reduced pressure. The resulting dark green solid was added to a dichloromethane solution (500 mL) containing Bu-pya (2.0 g, 12 mmol) and reacted for 30 minutes while applying ultrasonic waves. The resulting solution was filtered through silica gel and then concentrated to precipitate a dark green solid. The dark green powder obtained by suction filtration using a glass filter was washed with methanol and diethyl ether in that order and dried under reduced pressure to obtain compound 8. Yield 10%.

[0058] Elemental analysis results: Calc. for C 18 H 18 N 2 PdS 8 : C, 34.58; H, 2.90; N, 4.48. Found: C, 34.26; H, 2.89; N, 4.36%. l H-NMR (dimethyl sulfoxide-d 6, 50 °C): δ(ppm) 0.93 (t, 3H), 1.32 (m, 2H), 1.80 (t, 2H), 3.37 (s, 4H), 3.73 (t, 2H), 7.79 (t, 1H), 8.07 (d, 1H), 8.27 (t, 1H), 8.42 (d, 1H), 8.82 (s, 1H).

[0059] [ka]

[0060] (Compound 9) Compound 9 consists of a nitrogen-containing ligand N-butyl-pyridine-carbaldimine (Bu-pya) and a sulfur-containing ligand disulfanyl-1,3-dithiol-2-thionate(2-) (C 3 S 5 2- ) is an asymmetric metal complex in which palladium(II) ions are coordinated, and [(Bu-pya)Pd(C 3 S 5 )] (Non-Patent Document 2). The sulfur-containing ligand disulfanyl-1,3-dithiol-2-thionate(2-) is also written as 2-thione-1,3-dithiole-4,5-dithiolate.

[0061] Disulfanyl-1,3-dithiol-2-thionate(2-) (C 3 S 5 2- ) as a precursor of the ligand (NBu n 4 ) 2 [Zn(C 3 S 5 ) 2 ](480 mg, 0.50 mmol) (NBu n 4 = tetrabutylammonium cation) as the metal complex precursor, Pd(Bu-pia)Cl 2A solution of (530 mg, 3.3 mmol) (Bu-pya = N-butyl-pyridine-carbaldimine) in dichloromethane (50 mL) was stirred at room temperature for 2 hours to allow the reaction to proceed. Methanol (50 mL) was added to the resulting solution to precipitate a deep red solid. The resulting deep red solid was filtered and recrystallized in dichloromethane to obtain compound 9. Yield 22%.

[0062] Elemental analysis results: Calc. for C 13 H 14 N 2 PdS 5 : C, 33.58; H, 3.03; N, 6.02. Found: C, 33.33; H, 3.14; N, 5.90%. l H-NMR (dimethyl sulfoxide-d 6 , 50 °C): δ(ppm) 0.93 (t, 3H), 1.35 (m, 2H), 1.82 (t, 2H), 3.76 (t, 2H), 7.82 (t, 1H), 8.12 (d, 1H), 8.30 (t, 1H), 8.45 (d, 1H), 8.85 (s, 1H).

[0063] [ka]

[0064] (Compound 10) The compounds consist of the nitrogen-containing ligand 4,4'-dinonyl-2,2'-bipyridine (nonyl-bpy) and the sulfur-containing ligand 2-{(4,5-ethylenedithio)-1,3-dithiole-2-ylidene}-1,3-dithiole-4,5-ditholate(2-) (C 8 H 4 S 8 2- ) is an asymmetric metal complex in which platinum(II) ions are coordinated, and [(nonyl-bpy)Pt(C 8 H 4 S 8 )] (Non-Patent Document 5).

[0065] Under a nitrogen atmosphere, sodium methoxide (150 mg, 2.2 mmol) and the precursor of the sulfur-containing ligand 2-{(4,5-ethylenedithio)-1,3-dithiole-2-ylidene}-1,3-dithiole-4,5-ditholate (2-) (C 8 H 4 S 8 (C 2 H 4 CN) 2 ) (210 mg, 0.45 mmol) was dissolved in ethanol (30 mL). The resulting deep red solution was used as a metal complex precursor (nonyl-bpy)PtCl 2 (300 mg, 0.45 mmol) (nonyl-bpy = 4,4'-dinonyl-2,2'-bipyridine) in acetonitrile (12 cm 3 ) solution and reacted, and stirred for 75 minutes. The resulting dark green powder was filtered off under reduced pressure. The resulting dark green powder was dissolved in chloroform and purified by filtering through silica gel. The dark green solution obtained after filtration was concentrated, and methanol was added to precipitate a dark green powder. The dark green powder obtained by suction filtration using a glass filter was washed with methanol and diethyl ether in that order, and dried under reduced pressure to obtain compound 10. Yield 55%.

[0066] Elemental analysis results: Anal. Calc. for C 36 H 48 N 2 PtS 8 : C, 45.02; H, 5.04; N, 2.92. Found: C, 45.00; H, 5.02; N, 2.88%

[0067] [ka]

[0068] (Compound 11) Compound 11 is a complex of the nitrogen-containing ligand 4,4'-dinonyl-2,2'-bipyridine (nonyl-bpy) and the sulfur-containing ligand disulfanyl-1,3-dithiol-2-thionate(2-) (C 3 S 5 2- ) is an asymmetric metal complex in which platinum(II) ions are coordinated, and [(nonyl-bpy)Pt(C 3 S 5 )] (Non-Patent Document 5). The sulfur-containing ligand disulfanyl-1,3-dithiol-2-thionate(2-) is also written as 2-thione-1,3-dithiole-4,5-dithiolate.

[0069] Under a nitrogen atmosphere, sodium methoxide (150 mg, 2.2 mmol) and the sulfur-containing ligand disulfanyl-1,3-dithiol-2-thionate(2-) (C 3 S 5 2- ) precursor (C 3 S 5 {(CO)(C 6 H 5 )} 2 ) (180 mg, 0.44 mmol) in ethanol (20 mL) to obtain a deep red solution, which was then used as a metal complex precursor (nonyl-bpy)PtCl 2 (300 mg, 0.45 mmol) (nonyl-bpy = 4,4'-dinonyl-2,2'-bipyridine) in acetonitrile (12 cm 3 The resulting solution was added to the ethyl acetate solution and reacted with the solution and stirred for 60 minutes. The resulting purple powder was filtered under reduced pressure. The resulting purple powder was washed with methanol and diethyl ether in that order and dried under reduced pressure to obtain compound 11. Yield: 96%.

[0070] Elemental analysis results: Anal. Calc. for C 31 H 44 N 2 PtS 5, C, 46.54; H, 5.54; N, 3.50. Found: C, 46.54; H, 5.47; N, 3.31%.

[0071] [ka]

[0072] (Compound 12) Compound 12 is a complex of the nitrogen-containing ligand 4,4'-dinonyl-2,2'-bipyridine (nonyl-bpy) and the sulfur-containing ligand disulfanyl-1,3-dithiol-2-thionate(2-) (C 3 S 5 2- ) is an asymmetric metal complex coordinated to a palladium(II) ion, [(nonyl-bpy)Pd(C 3 S 5 The sulfur-containing ligand disulfanyl-1,3-dithiol-2-thionate(2-) is also written as 2-thione-1,3-dithiole-4,5-dithiolate.

[0073] Under a nitrogen atmosphere, sodium methoxide (150 mg, 2.2 mmol) and the sulfur-containing ligand disulfanyl-1,3-dithiol-2-thionate(2-) (C 3 S 5 2- ) precursor (C 3 S 5 {(CO)(C 6 H 5 )} 2 ) (180 mg, 0.44 mmol) in ethanol (20 mL) to obtain a deep red solution, which was then treated with the metal complex precursor (nonyl-bpy)PdCl 2 (300 mg, 0.45 mmol) (nonyl-bpy = 4,4'-dinonyl-2,2'-bipyridine) in acetonitrile (12 cm 3The mixture was added to the 1,2-dichlorophenyl ether (1,2-dichlorophenyl ether) solution, reacted, and stirred for 60 minutes. The resulting purple powder was filtered under reduced pressure. The resulting purple powder was washed with methanol and diethyl ether in that order, and dried under reduced pressure to obtain compound 12. Yield: 96%.

[0074] [ka]

[0075] (Compound 13) Compound 13 is an asymmetric metal complex in which the nitrogen-containing ligand 4,4'-dinonyl-2,2'-bipyridine 2-{(4,5-ethylenedithio)-1,3-dithiole-2-ylidene}-1,3-dithiole-4,5-ditholate(2-) is coordinated to a palladium(II) ion, [(nonyl-bpy)Pd(C 8 H 4 S 8 )] is written as

[0076] Under a nitrogen atmosphere, sodium methoxide (150 mg, 2.2 mmol) and the precursor of 2-{(4,5-ethylenedithio)-1,3-dithiole-2-ylidene}-1,3-dithiole-4,5-ditholate (2-) (C 8 H 4 S 8 (C 2 H 4 CN) 2 ) (180 mg, 0.44 mmol) was dissolved in ethanol (20 mL). The resulting deep red solution was treated with the metal complex precursor (nonyl-bpy)PdCl 2 (300 mg, 0.45 mmol) (nonyl-bpy = 4,4'-dinonyl-2,2'-bipyridine) in acetonitrile (12 cm 3 The mixture was added to the 1,2-dichlorophenyl ether (1,2-dichlorophenyl ether) solution, reacted, and stirred for 60 minutes. The resulting purple powder was filtered under reduced pressure. The resulting purple powder was washed with methanol and diethyl ether in that order, and dried under reduced pressure to obtain compound 13. Yield: 96%.

[0077] Elemental analysis results: Anal. Calc. for C 36 H 48 N 2 PdS 8 : C, 45.02; H, 5.04; N, 2.92. Found: C, 45.00; H, 5.02; N, 2.88%.

[0078] [ka]

[0079] <Preparation of electrochromic layer> Compounds 1 to 12 were dissolved in ultra-dehydrated chloroform (Fujifilm Wako Pure Chemical Industries, Ltd.) at 2.1 × 10 -2 mol L -1 The concentration of each solution was adjusted to 0.5 mL on an ITO glass substrate (0.5 cm x 2 cm, Geomatec Co., Ltd.) attached to a spin coater (Kyowa Riken Co., Ltd., K-359S1). Then, the solution was spin-coated at 1500 rpm for 20 seconds to form an electrochromic layer on the ITO glass substrate.

[0080] The solubility of each compound in ultra-dehydrated chloroform solution was visually confirmed. In addition, the state of the electrochromic layer (thin film) formed on the ITO glass substrate was visually confirmed. Figure 1 shows a photograph of the appearance of the electrochromic layer (thin film) of compound 2 formed on the ITO glass substrate.

[0081] Table 1 shows the solubilities of compounds 1 to 13 in ultra-dehydrated chloroform solutions and the state of the electrochromic layer formed on the ITO glass substrate.

[0082] [Table 1]

[0083] Compounds 2, 5, 10, 11, 12, 13 were completely dissolved in ultra-dehydrated chloroform at 2.1 × 10 -2 mol L -1 However, other compounds were poorly soluble and remained undissolved, resulting in a concentration of 2.1 × 10 -2 mol L -1 It was not possible to prepare a spin coating solution having a concentration of 1.

[0084] Of the highly soluble compounds 2, 5, and 10 to 13, compound 2 and 5 formed a uniform electrochromic layer (thin film). Compound 10 also formed an electrochromic layer (thin film), but compared to compounds 2 and 5, the film was very light in color. Compounds 11 and 12 also formed electrochromic layers that were not uniform and had irregularities. Compound 13 precipitated crystalline fine particles and did not form a thin film. Compounds 1, 3, 4, 6 to 9, which had low solubility, also formed thin films by spin coating, but undissolved powder precipitated on the surface of the thin film.

[0085] Concentration 2.1 × 10 -2 mol L -1 If the concentration is less than 2.1 × 10, a spin coating solution in which even compounds with low solubility are completely dissolved can be prepared. -2 mol L -1 When a spin-coating solution with a concentration of less than 2.1 × 10 was used, a thin film was not formed on the ITO glass substrate. Therefore, in order to prepare a thin film of the asymmetric metal complexes of compounds 1 to 13 on an ITO substrate, a concentration of 2.1 × 10 -2 mol L -1 It is necessary to prepare a spin-coating solution with a concentration equal to or greater than 1000 ppm. Similar results were obtained when ultra-dehydrated dichloromethane was used as the solvent.

[0086] <Measurement of electrochromic properties (three-electrode electrochromic device)> A quartz electrochemical measurement cell (optical path length 1 cm, Hokuto Denko Corporation) was filled with 2 mL of the ionic liquid (1-butyl-3-methylimidazolium bis(trifluoro-methylsulfonyl)imide) shown below. An ITO glass substrate on which electrochromic layers (thin films) of compounds 1 to 12 were formed, a platinum counter electrode (Hokuto Denko Corporation), and an Ag / AgCl reference electrode (Hokuto Denko Corporation) were attached to the cell to assemble a measurement cell (three-electrode electrochromic device). A schematic diagram of the measurement cell is shown in Figure 2. Note that a measurement cell was not prepared for compound 13 because it was difficult to prepare a thin film.

[0087] [ka]

[0088] The ITO glass substrate, platinum counter electrode, Ag / AgCl reference electrode and reference electrode of the measurement cell were connected to an electrochemical analyzer, BAS potentiostat ALS / [H] CH Instruments Electrochemical Analyzer Model 612C, with a copper wire for measurement. Next, the measurement cell connected to the electrochemical analyzer was attached to an ultraviolet-visible spectrophotometer (JASCO V-670). As a reference, a reference cell was used in which only 2 mL of ionic liquid (1-butyl-3-methylimidazolium bis(trifluoro-methylsulfonyl)imide) was filled in the same quartz cell as the measurement cell.

[0089] A schematic diagram of the measurement device is shown in Fig. 3. A conceptual diagram showing the light transmission direction for the cells in the spectrophotometer is shown in Fig. 4. Light from the light source transmits vertically through the electrochromic layer 11 (thin film) of the working electrode 2 in the measurement cell, and transmits vertically through the thickness direction of the ITO glass substrate 10 in the reference cell.

[0090] Table 2 shows the color change, color unevenness, and infrared region change of compounds 1 to 12 measured on the three-electrode electrochromic device (three-electrode device). All of these items were confirmed visually. The electrochemical analyzer was used to control the voltage between the working electrode and the platinum counter electrode. In addition, the spectrophotometer was used to measure the electrochromic behavior as an actual wavelength change, rather than visually.

[0091] [Table 2]

[0092] Among compounds 1 to 12, compounds 2, 5, 11, and 12 were confirmed to have a clear color change. Compound 10 also showed a color change, but the visual contrast was very poor compared to compounds 2, 5, 11, and 12. Among these compounds, compounds 2 and 5 were not uneven in color. Compounds 2, 5, 11, and 12 were also confirmed to have a color change in the infrared region.

[0093] Figure 5 shows the color change in the neutral, one-electron acid, and two-electron oxidation states of compounds 2, 5, 10, 11, and 12. By performing electrochemical measurements in the solution state of each compound, the redox potential of the molecule itself can be known. When comparing electrochemical measurements in the solution state and the solid state, the redox potential and wave shape may differ due to molecular association, etc., but for compounds 2, 5, 10, 11, and 12, the electrochemical measurements obtained in the solution state and the solid state were consistent. Therefore, based on each potential obtained from the electrochemical measurements, a voltage was applied between the ITO electrodes to determine the color tone in each oxidation state.

[0094] Compounds 2 and 5 showed clear color changes, but compound 10 showed little color change in response to applied voltage, and the contrast was very unclear, although there was no unevenness in the color. Compounds 11 and 12 showed color changes from purple to green and from reddish purple to green, respectively. Compounds 11 and 12 are compounds that differ only in the metal ion, and from these results it is presumed that color tuning is possible by exchanging metal ions. However, because the film thickness of compounds 11 and 12 was non-uniform, color unevenness due to residual particles was confirmed depending on the position in the thin film.

[0095] From the above experimental results, it was found that, among compounds 1 to 13, compounds 2 and 5 were capable of forming uniform thin films and showed clear changes in color tone.

[0096] The surfaces of the thin films of compounds 2 and 5 were observed and their thicknesses were measured. A medium-sized probe microscope system AFM 5500M manufactured by Hitachi High-Tech Corporation was used for surface observation, and a scanning white light interference microscope VS1550 manufactured by Hitachi High-Tech Corporation was used for thickness measurement. The average thicknesses of the films were 120 nm for compound 2 and 150 nm for compound 5.

[0097] In addition, for compounds 11 and 12, in which a change in color tone was confirmed, although the change in color tone was uneven due to the formation of an uneven thin film, the average film thickness was 350 nm and 120 nm, respectively. Therefore, in order to cause a clear color change, the electrochromic layer must have a film thickness of at least 100 nm.

[0098] The redox potential of the thin film of compound 2 was measured in the range of -0.5 to +1.2 V (vs. Ag / AgCl) at a sweep rate of 0.01 V / sec. The results are shown in Figure 6. Figure 6(a) shows the results of a 3-cycle measurement, and Figure 6(b) shows the results of an 8-cycle measurement. Basically, a wave caused by two-electron redox was observed, and electrochromic behavior was also observed in association with this redox. The peak current value of the wave caused by one-electron and two-electron redox increased as the number of sweeps increased, suggesting that the electron transfer was promoted by increasing the number of sweeps.

[0099] From the wave shape shown in Figure 6, it was confirmed that the transfer of two electrons (oxidation-reduction) occurs between the electrode and the thin film even in the thin film state. In addition, since the electron transfer occurs reversibly, it was also confirmed that the thin film of compound 2 exhibits stable electrochromic behavior.

[0100] Figure 7 shows the spectral changes in the oxidation and reduction processes of compound 2 when voltages of -0.5, +0.2, and +1.2 V (vs. Ag / AgCl) were applied. Figure 7(a) shows the oxidation process, and Figure 7(b) shows the reduction process. The electrochromic behavior observed by visual observation showed a clear change from green to orange to blue-green, confirming the multicolor electrochromic behavior of three or more colors due to the asymmetric metal complex (compound 2). This color change is due to the reversible change in the absorption band seen from 400 nm to 700 nm. In concert with this change in the visible light region, a very wide change in the absorption band was also seen in the wavelength range above 700 nm. In particular, a large change in the absorption band appeared from 700 nm to 1200 nm.

[0101] The results of the measurement of the redox potential of the thin film of compound 5, measured at a sweep rate of 0.01 V / sec in the range of -0.2 to +1.5 V (vs. Ag / AgCl), are shown in Figure 8. Figure 8(a) shows the results of a 3-cycle measurement, and Figure 8(b) shows the results of a 9-cycle measurement. Basically, a wave caused by the redox of two electrons was observed, and electrochromic behavior was also observed along with this redox. Since the peak current value of the wave caused by the redox of one electron and two electrons increased as the number of sweeps increased, it was considered that the electron transfer was promoted by increasing the number of sweeps. In addition, in Figure 8(b), the redox wave of the redox potential tended to be unstable only in the first cycle, but it was confirmed that the redox wave was stable in the second to ninth cycles.

[0102] Figure 9 shows the spectral changes of compound 5 when voltages of -0.2, +0.71, and +1.2 V (vs. Ag / AgCl) were applied during the oxidation process, and voltages of +1.2 V, +0.44, and -0.2 V (vs. Ag / AgCl) were applied during the reduction process. Figure 9(a) shows the oxidation process, and Figure 9(b) shows the reduction process. The electrochromic behavior observed by visual observation showed a clear change from reddish brown to yellow-orange to blue, and multi-color electrochromic behavior was confirmed in compound 5, which exhibited three or more colors. This color change is due to a reversible change in the absorption band seen from 400 nm to 600 nm. The change in the absorption band in the visible light region shown by compound 5 shows a different spectral behavior from the change in the absorption band shown by compound 2, so it was thought that color tuning is possible by combining metal ions and ligands. In concert with this change in the visible light region, a very wide change in the absorption band was also observed in the wavelength range of 600 nm or more. In particular, a large change in the absorption band was observed in the range from 600 nm to 1000 nm.

[0103] The switching characteristics of compound 2 were measured at 584 nm in the visible light region and 892 nm in the near infrared region at applied voltages of +0.9 V (vs. Ag / AgCl) and +0.35 V (vs. Ag / AgCl) with a pulse width of 10 seconds. The results are shown in Figure 10. Figure 10(a) shows the oxidation process, and Figure 10(b) shows the reduction process. Compound 2 has switching performance equivalent to conventional electrochromic compounds based on organic polymer materials or metal oxides in both the visible light region and the near infrared region, and Figure 10 suggests that it is an electrochromic material that can be used for displays and other applications.

[0104] The switching characteristics of compound 5 in the visible light region of 660 nm were measured at applied voltages of +0.6 V (vs. Ag / AgCl) and -0.5 V (vs. Ag / AgCl) and a pulse width of 10 seconds. The switching characteristics in the near-infrared region of 900 nm were also measured at applied voltages of +1.2 V (vs. Ag / AgCl) and +0.6 V (vs. Ag / AgCl) and a pulse width of 10 seconds. The results of these measurements are shown in Figures 11(a) and (b), respectively. Compound 5, like compound 2, has switching performance equivalent to conventional electrochromic compounds based on organic polymer materials or metal oxides in both the visible light region and the near-infrared region, and Figure 11 suggests that it is an electrochromic material that can be applied to displays, etc.

[0105] Conventional electrochromic devices capable of concerted changes in the visible light region and near-infrared region require complex manufacturing processes, such as the need to form multiple electrochromic layers, as disclosed in Non-Patent Document 6. However, compounds 2 and 5 can achieve concerted electrochromic behavior in the visible light region and near-infrared region with only an electrochromic thin film consisting of a single layer of a low molecular weight compound, making it possible to greatly simplify the device manufacturing process.

[0106] In this way, it has become clear that the wavelength region in which electrochromic behavior is expressed can be changed by changing the metal ion or ligand of the asymmetric metal complex. Therefore, tuning of color tone (e.g., Non-Patent Document 1), which was said to be difficult in conventional electrochromic devices based on organic polymer materials or metal oxides, can be realized by combining the ligand and metal ion of the electrochromic compound of the present invention, and device development toward practical use of electrochromic displays, etc. can be advanced.

[0107] <Measurement of electrochromic properties (two-electrode electrochromic device)> After preparing an ITO glass substrate on which an electrochromic layer (thin film) was formed, the substrate was masked with Kapton tape, and then an electrolyte gel consisting of 0.5 g of Poly(ethylene glycol) dimethacrylate, 0.5 g of Poly(ethylene glycol) methyl ether acrylate, and 0.1 g of Lithium Trifluoromethanesulfonate was applied onto the electrochromic layer by a drop-cast method (thickness 120 μm) to form an electrolyte layer. Another sheet of ITO glass was laminated on this electrolyte layer, and a two-electrode electrochromic device (two-electrode device) was prepared in which the electrochromic layer and the electrolyte layer were sandwiched between the two sheets of ITO glass. Figure 12 shows a schematic diagram of the two-electrode electrochromic device prepared. In this device, the upper ITO glass substrate 2 functions as a counter electrode.

[0108] A reference device was prepared in the same manner as the two-electrode device, in which only the electrochromic layer was sandwiched between two sheets of ITO glass. The two-electrode device and the reference device were set in the spectrometer shown in FIG. 13, and a voltage was applied between the working electrode and the counter electrode of the two-electrode device to measure the electrochromic behavior of compounds 1 to 12. Compound 13 was excluded from the measurement because it was difficult to prepare a thin film of it. A potentiostat ALS / [H] CH Instruments Electrochemical Analyzer Model 612C manufactured by BAS was used as the electrochemical analyzer, and a V-670 manufactured by JASCO was used as the ultraviolet-visible spectrophotometer.

[0109] The color change of Compounds 1 to 12 measured in the same manner as the three-electrode device and the state of the two-electrode device are shown in Table 3. The electrochemical analyzer was used to control the voltage between the two opposing ITO electrodes. In addition, the spectrophotometer was used to measure the electrochromic behavior as an actual wavelength change, not by visual observation.

[0110] [Table 3]

[0111] The electrochromic measurements in the two-electrode device showed the same tendency as in the three-electrode device. Because a voltage is applied between the two opposing electrodes, the electrochromic behavior is considered to be greatly influenced by the state of the thin film. Compounds 2 and 5 showed a clear color change, but the other compounds had a poor response to the voltage application, and the color change was very unclear to the naked eye.

[0112] Thus, among compounds 1 to 13, compounds 2 and 5 were capable of fabricating a two-electrode device and showed a clear color change.

[0113] Figure 14 shows the results of measuring the electrochromic behavior when a voltage was reversibly applied between the working electrode 1 and the counter electrode 2 of the two-electrode device of compound 2 in the range of +2.0 V to -1.4 V, with the starting potential set to 0 V. The voltage sweep rate was 0.01 V / sec.

[0114] 14, it was confirmed that the two-electrode device of compound 2 exhibited concerted electrochromic behavior in the visible light region of 400 nm to 700 nm and the near-infrared region of 700 nm to 1200 nm, similar to the three-electrode device. The change in color from green to orange to blue-green was also confirmed by visual observation, and compound 2 was found to be an asymmetric metal complex molecule that can be applied to electrochromic devices.

[0115] 15 shows the results of measuring the electrochromic behavior when the potential between the working electrode 1 and the counter electrode 2 of a two-electrode device of Compound 5 was changed from a starting potential of 0 V to +3.0 V via +1.8 V based on 0 V, the potential was then reversed, and the compound was reduced to -1.4 V via +1.8 V, and then oxidized again to 0 V. The voltage sweep rate was 0.01 V / sec.

[0116] From FIG. 15, it was confirmed that the two-electrode device of compound 5 exhibited concerted electrochromic behavior in the visible light region of 400 nm to 600 nm and the near-infrared region of 600 nm to 1000 nm, similar to the two-electrode device. The change from reddish brown to yellow-orange to blue was also confirmed by visual inspection, and it was found that compound 5 is an asymmetric metal complex molecule that can be applied to electrochromic devices. In addition, the absorption bands in which the electrochromic behavior of compound 5 is observed are different from the absorption bands in the electrochromic behavior of compound 2, and it was concluded that color tuning is possible by combining metal ions and ligands, similar to the measurement of the three-electrode device.

[0117] Table 4 shows the electrochromic behavior of Compound 2 measured by a two-electrode electrochromic device and the concerted changes in the visible light and near infrared spectra. Table 5 shows the electrochromic behavior of Compound 5 measured by a two-electrode electrochromic device and the concerted changes in the visible light and near infrared spectra.

[0118] [Table 4]

[0119] [Table 5]

[0120] From Tables 4 and 5, compounds 2 and 5 exhibited the same concerted electrochromic behavior in the visible light / near infrared region as that exhibited in the three-electrode device, also in the two-electrode device. Compared to the three-electrode device, the two-electrode device tended to show a slightly delayed change in color tone in response to the voltage sweep. However, many of the light-shielding glasses for aircraft that have already been put into practical use (e.g., Patent Documents 1 and 2) have a response time of several seconds. For this reason, it is believed that two-electrode electrochromic devices using asymmetric metals such as compounds 2 and 5 can also be used in practical applications such as light-shielding materials or light-controlling glasses.

[0121] To examine the stability of electrochromic devices using compounds 2 and 5, the switching behavior at each wavelength was measured. For compound 2, +1.2 V and -1.4 V were applied alternately at 30 second intervals, and the change in absorbance was measured at 584 nm in the visible light region and 1020 nm in the near infrared region. For compound 5, +1.2 V and +2.9 V were applied alternately at 10 second intervals at 730 nm in the visible light region and 940 nm in the near infrared region, and the change in absorbance was measured.

[0122] The switching behavior of compound 2 is shown in Figure 16. Figure 16(a) shows the switching behavior at 584 nm (visible light region), and Figure 16(b) shows the switching behavior at 1020 nm (near infrared region). As shown in Figures 16(a) and (b), stable switching behavior was confirmed for more than 1200 seconds. However, compared to the three-electrode device, the two-electrode device showed a smaller change in absorbance and a tendency for the response speed to be slightly slower.

[0123] The switching behavior of compound 5 is shown in Figure 17. (a) shows the switching behavior of compound 5 at 730 nm (visible light region), and (b) shows the switching behavior of compound 5 at 940 nm (near infrared region). As shown in Figures 17(a) and (b), stable switching behavior was confirmed for more than 400 seconds. However, similar to the switching behavior of compound 2, the two-electrode system device showed a smaller change in absorbance and a tendency for the response speed to be slightly slower than the three-electrode system measurement.

[0124] (Effect of alkyl groups on thin film properties) A nonyl group was added to the bipyridine moiety, and C was added as a dithiolene ligand. 3 S 5 Compounds 10 and 11, which have ligands, formed thin films, although they were not uniform. However, the asymmetric metal complexes with nonyl groups at the bipyridine moiety also formed thin films with C 8 H 4 S 8 Compound 12, a ligand-bound platinum complex, formed only a very thin film. In addition, an asymmetric metal complex with a nonyl group at the bipyridine moiety, C 8 H 4 S 8 Compound 13, a palladium complex with a ligand bonded to it, was a highly crystalline compound and crystallized on the ITO substrate without forming an amorphous thin film. Compounds 1, 4, 6, and 7, which do not have an alkyl group in the asymmetric metal complex moiety, and compounds 3, 8, and 9, which have a butyl group, did not form a thin film suitable for electrochromic devices.

[0125] (Evaluation of electrochromic behavior) A nonyl group was added to the bipyridine moiety, and C was added as a dithiolene ligand. 3 S 5 Compounds 10 and 11, which have ligands, exhibited electrochromic behavior that showed two-color color tone changes when observed in a three-electrode device. However, color unevenness was observed in the color tone change due to the non-uniformity of the thin film. 8 H 4 S8 Compound 12, a ligand-bound platinum complex, showed only very unclear electrochromic behavior, whereas compounds 2 and 5, which have decyl groups, showed clear three-color multicolor electrochromic behavior.

[0126] (Suitable Electrochromic Compounds) In this way, it was confirmed that, among compounds 1 to 13, compounds 2 and 5 have all the properties suitable for an electrochromic compound. When the chemical formulas of compounds 2 and 5 are compared with the chemical formulas of the other compounds, it was considered that the electrochromic compound used in the present invention must have a structure represented by the general formula of chemical formula 1.

[0127] (Electrode substrate) In the above embodiment, the working electrode is fabricated by forming the electrochromic layer on the ITO glass by spin coating, but the substrate of the working electrode may be a substrate such as FTO. The electrochromic layer may also be formed on the substrate by a method such as drop casting or spray coating. The substrate of the counter electrode may be a substrate such as ITO or FTO.

[0128] (Preferred electrolyte) The electrolyte used in the present invention is preferably an ionic liquid, a polymer gel, or a photopolymerizable or thermally polymerizable polymer solid. Of these, from the viewpoint of electrochromic thin film stabilization, an ionic liquid is most preferable. In a two-electrode electrochromic device, the thickness of the electrolyte layer is preferably about 100 nm to 200 nm. In a three-electrode electrochromic device, a working electrode, a counter electrode, and a reference electrode are stored in a cell filled with an electrolyte, and although the electrolyte is not layered, the distance between the working electrode and the counter electrode is preferably 2 to 5 mm. [Industrial Applicability]

[0129] The electrochromic device of the present invention is useful in technical fields such as display elements such as displays, and light control glass. [Explanation of symbols]

[0130] 1: Quartz cell 2: ITO glass substrate 3: Electrolyte layer (ionic liquid) 4: Counter electrode (platinum mesh) 5: Reference electrode (Ag / AgCl) 6: Copper wire for connection 7: Electrochemical analyzer 8: Spectrophotometer 9: Reference cell 10: Electrochromic layer 11: Kapton tape 12: Reference device 13: Two-electrode device 14: Measuring cell 15: Working electrode

Claims

1. A working electrode; A counter electrode; An electrolyte layer; and an electrochromic layer made of an electrochromic compound having a structure of Chemical Formula 2 or Chemical Formula 3, the electrolyte layer and the electrochromic layer are sandwiched between the working electrode and the counter electrode; The electrochromic layer is formed so as to be in contact with the working electrode, The electrolyte layer is formed so as to be in contact with the counter electrode, A voltage is applied between the working electrode and the counter electrode to change the color of the electrochromic layer. Electrochromic device. 【Chemistry 1】 【Chemistry 2】

2. A cell, A working electrode; A counter electrode; A reference electrode; An electrolyte; An electrochromic layer made of an electrochromic compound having a structure of Chemical Formula 2 or Chemical Formula 3; having The working electrode has the electrochromic layer formed on one surface of a substrate, the counter electrode and the reference electrode are located in the cell at positions opposite the electrochromic layer of the working electrode; The cell is filled with the electrolyte, A voltage is applied between the working electrode and the counter electrode to change the color of the electrochromic layer. Electrochromic device. 【Chemistry 3】 【Chemistry 4】

3. 3. The electrochromic device according to claim 1, wherein the electrochromic layer has a thickness of 10 nm or more and 1000 nm or less.

4. 2. The electrochromic device of claim 1, wherein the electrolyte layer has a thickness of 100 nm or more and 200 μm or less.

5. 5. The electrochromic device according to claim 1, wherein the electrolyte layer is an ionic liquid, a polymer gel, a photopolymerizable polymer solid, or a thermally polymerizable polymer solid.

Citation Information

Patent Citations

  • Electrochromic windows and method of manufacturing the same

    EP1330678A1

  • JP12845A

  • Developing device in electrophotographic copier

    JP1980002264A

  • Manufacture of interlayer compound, interlayer compound, and electrochromic display element using the same

    JP1998239714A

  • Electrochromic device and display method using the same

    JP2007047582A